Wāhkōhtowin: Decolonising Teacher Preparation for Rural, Urban and First Nations Schools - Wallin, Dawn; Scribe, Chris (Australian and International Journal of Rural Education, 2022)
This paper stories the creation of the Wāhkōhtowin teacher preparation model on Treaty 6 territory in Saskatchewan, Canada. The model was created out of an educational partnership that responded to the teachings of Nēhiyaw (Cree) Indigenous Elders. We describe the theoretical framework of this Professional Development School (PDS) teacher preparation model that is designed to decolonize teacher preparation in order to foster student learning and engagement; develop Nēhiyaw teacher identity and proficiency, and; support reconciliation between Indigenous and non-Indigenous peoples. The foundational constructs of the Wāhkōhtowin model of teacher preparation include relationality, ceremony, language, and child-centredness. The spirit of Wāhkōhtowin teacher preparation is premised on three intents. Firstly, teacher candidates are encouraged to be free to be themselves and share the gifts they bring to the school setting (tipéyimisowin). Secondly, they are encouraged to ‘come home’ to traditional teachings as they engage in cultural learning and identity formation (kīwēwin). Thirdly, their pedagogical growth and development as teachers is fostered with the focus on relational pedagogies, inclusiveness, and community (mamáwi kiskinomāsowin). We complete our paper by discussing the implementation of the Wāhkōhtowin model. We discuss the ways in which the model has had to shift to be responsive to the unique relationships and contexts of different school systems, provincial budget cuts, the opportunity to expand the program into secondary schools, working with/through teacher turnover, the provision of language and cultural activities, land-based programming, professional development sessions, differing comfort levels and knowledge regarding Indigenous history and traditions, and the impact of COVID-19.